Employer branding peculiarities from a generational perspective: case of Baltic states - Apsite, Annija (University of Latvia, 2021)
Companies have currently acknowledged that it does matter, how current and potential employees see them. Several companies see that they can develop their competitive advantage by creating and sustaining an attractive image of the company. It takes more than beautiful promises, future illusions and lovely pictures of the company – it has to be a culture based on certain values, which are attractive for the potential and current employees. It certainly is especially important for companies, who are operating in fields, where there is a lack of high skilled workers and where headhunting is inevitable. In the existing literature most of the researches are about attracting employees. However, being able to attract is as equally important as being able to create and sustain the loyalty of the current employees since low job satisfaction leads to high employee turnover and thus lower productivity. The aim of the research is determine, which are the most important work-related factors, which employees evaluate as attractive. The method used in the research is survey method with over 6000 respondents from the Baltic States. The results show that there are statistically significant differences among different age groups – although almost all given factors were evaluated as either very important or rather important by all age groups, there are different priorities depending on the age and stage of the career of respondents.
Keywords: employer brand; organizational values; job satisfaction; Research Subject Categories::SOCIAL SCIENCES